2001
DOI: 10.1021/bi010923m
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Specific Target Recognition and RNA Hydrolysis by Ribonucleolytic Toxin Restrictocin

Abstract: Restrictocin, a member of the fungal ribotoxin family, specifically cleaves a single phosphodiester bond in the 28S rRNA and potently inhibits eukaryotic protein synthesis. Residues Tyr47, His49, Glu95, Phe96, Pro97, Arg120, and His136 have been predicted to form the active site of restrictocin. In this study, we have individually mutated these amino acids to alanine to probe their role in restrictocin structure and function. The role of Tyr47, His49, Arg120, and His136 was further investigated by making addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 36 publications
0
19
0
Order By: Relevance
“…The E105A mutation abolishes RegB toxicity, and E19A and E19V lower it. Previous mutagenesis experiments with other ribonucleases (including YoeB) showed that mutants of the general base conserved residual activity (30,32,33 19 and His 48 C ␤ is slightly too long. This could be related to the observation that RegB is catalytically a "very poor" enzyme and could suggest that the formation of a productive enzyme-substrate complex involves, after a first rapid binding step, an infrequent rearrangement of the protein structure.…”
Section: Discussionmentioning
confidence: 99%
“…The E105A mutation abolishes RegB toxicity, and E19A and E19V lower it. Previous mutagenesis experiments with other ribonucleases (including YoeB) showed that mutants of the general base conserved residual activity (30,32,33 19 and His 48 C ␤ is slightly too long. This could be related to the observation that RegB is catalytically a "very poor" enzyme and could suggest that the formation of a productive enzyme-substrate complex involves, after a first rapid binding step, an infrequent rearrangement of the protein structure.…”
Section: Discussionmentioning
confidence: 99%
“…It recognized and cleaved a single phosphodiester bond specifically in a GAGA tetranucleotide located in a conserved stem and loop structure in ribosomal RNA (Nayak et al 2001). The active site of restrictocin for its ribonucleolytic activity is shown in Fig.…”
Section: Fungal Proteins and Peptides With Antiviral Activitymentioning
confidence: 99%
“…The IC 50 of ␣-sarcin has been shown to be in the range of 0.4-10 M for different cell lines [6]. However, ribotoxins potently inhibit protein synthesis in permeabilized cells, and therefore are much more toxic to them [7][8][9]. Restrictocin is a non-glycosylated, basic, single chain protein of 149 amino acids with a molecular weight of 16.8 kDa [2,10].…”
Section: Introductionmentioning
confidence: 99%
“…They only cleave a single phosphodiester bond in 28s rRNA sparing all other cellular RNAs. The specific target recognition ability of restrictocin has been shown to be through a histidine residue at position 49, substitution of which results in the loss of specificity though the RNase activity of the protein is maintained [8,9]. The catalytic apparatus of restrictocin is similar to that of pyrimidine specific RNases of the RNase A superfamily, and histidine at position 136 has been shown to be absolutely essential for the ribonucleolytic activity of restrictocin [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation